Peran Organizational Citizenship Behavior (OCB), Disiplin Kerja dan Quality of Work Life (QWL) dalam Meningkatkan Kinerja Pegawai melalui Motivasi Kerja pada Inspektorat Kabupaten Sukoharjo - Lilis Sulistyani; Oviandreva Ningrum (ProBank, 2025)
The purpose of this study was to determine, test and empirically analyze the significance of organizational citizenship behavior, work discipline and quality of work life on work motivation and employee performance at the Sukoharjo Regency Inspectorate. The population in this study were 40 employees at the Sukoharjo Regency Inspectorate. The data collection technique was a questionnaire. The sample with the census technique was 40 respondents. Data analysis was carried out using instrument tests, linearity tests, hypothesis tests, and path analysis. The results is OCB and QWL have a positive and significant effect on employee work motivation, but work discipline has a positive and insignificant effect on employee work motivation; OCB, work discipline and work motivation have a positive and significant effect on employee performance, but QWL has a positive and insignificant effect on employee performance. The results of the F test prove that OCB, work discipline, QWL and work motivation have a significant effect on employee performance at the Sukoharjo Regency Inspectorate. The total R2 value of 0.976 means that employee performance is explained by OCB, work discipline, QWL and work motivation by 97.6% and the remaining 2.4% is explained by other variables outside the research model. The results of the path analysis show that the direct path or direct influence of work discipline on employee performance is the dominant path in improving employee performance. The use of intervening variables of work motivation is effective as a mediator of the influence of the QWL variable on employee performance, but is not effective as a mediator of the influence of the OCB and work discipline variables on employee performance.